2013
DOI: 10.1016/j.micromeso.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Designing hierarchical porous features of ZSM-5 zeolites via Si/Al ratio and their dynamic behavior in seawater ion complexes

Abstract: MFI-type zeolites were characterized using powder x-ray diffraction (XRD), and positron annihilation lifetime spectroscopy (PALS) to uncover the hierarchical porous * Corresponding author. Tel: +61 3 9919 7682; fax: +61 3 9919 7696. Email: mikel.duke@vu.edu.au (M. Duke). overall release of ions, principally Na + and K + , which were liberated mainly from the zeolite channels, yet these materials adsorbed Ca 2+ in the microporous grain boundaries and Mg 2+ in the mesoporous grain boundaries. Si/Al = 100 appeare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
26
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 42 publications
8
26
1
Order By: Relevance
“…It is also worth pointing out that the He/N 2 selectivity of 3.5 is larger than the Knudsen model value of 2.6 suggesting even the zeolitic pores are sufficiently blocked to allow size selective diffusion of He over N 2 within the MFI intrinsic pores. The finding that ions block pores via this membrane diffusion study aligns with our materials investigation of the influence of ions on MFI-structures [25,26]. As discussed earlier, it appears temperature accelerated this effect.…”
Section: Gas Permeationsupporting
confidence: 89%
See 2 more Smart Citations
“…It is also worth pointing out that the He/N 2 selectivity of 3.5 is larger than the Knudsen model value of 2.6 suggesting even the zeolitic pores are sufficiently blocked to allow size selective diffusion of He over N 2 within the MFI intrinsic pores. The finding that ions block pores via this membrane diffusion study aligns with our materials investigation of the influence of ions on MFI-structures [25,26]. As discussed earlier, it appears temperature accelerated this effect.…”
Section: Gas Permeationsupporting
confidence: 89%
“…Several researchers have reported changes in the unit cell dimensions of MFI-type zeolite crystals during heat treatment [21][22][23][24]. Our recent studies [25,26] also showed that the interaction between MFI-type zeolites and the major cations in seawater causes changes not only in structure but also porosity, which is expected to affect diffusion properties of these materials when used as membranes for desalination. An easily modified feature of MFI-type zeolites is the Si/Al ratio which allows structures to be tailored to optimize the sorption uptake and species selectivity [27].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Thus from this data, we can conclude that SAPO-34 preferably expels the larger Al ions to accommodate smaller divalent, and to a larger extent monovalent ions, into the structure. This is in contrast to MFI-type zeolite where we found that divalent ions were taken in at the expense of monovalent ions at low alumina content [32,37]. However, it is important to mention that at higher alumina content MFI-type zeolite (ZSM-5) we see similar behaviour, in particular the release of Na [37] suggesting uptake of ions is stronger in higher alumina materials like SAPO-34.…”
Section: Membrane Desalination Testingcontrasting
confidence: 67%
“…In addition, their chemical composition and reactivity can be varied. Such materials have recently been employed as membrane materials [6][7][8][9][10]. We select zeolites that have pore sizes that are sufficiently small that small ions and molecules are expected to be excluded from the pores due to a molecular sieving effect, and focus on the diffusion coefficients of water in these materials.…”
Section: Introductionmentioning
confidence: 99%